The Determinants of Tax Compliance in Tax Amnesty Programs: Experimental Approach - Puri Mahestyanti; Bambang Juanda; Lukytawati Anggraeni (Faculty of Economic and Business, 2018)
In an effort of searching for a new source of revenue for funding the infrastructure development for Indonesia, the government chose to do tax amnesty in 2016. This research was conducted to study the effects of factors (wealth, tariff periods, tax penalties, and audit probability) towards tax compliance. Tax compliance measured from the number of units reported by taxpayers, the amount of value indicated by taxpayers, and participation from taxpayers. The study uses primary data that generated through experimental economics. The methods used are Variance Analysis. The result showed that the taxpayer with higher income has lower compliance rather than the taxpayer from lower income. The taxpayers prefer to report their assets at lower rates. The effort of enforcement from the government by implementing tax penalties and audit probability shows greater effect towards tax compliance.DOI: 10.15408/etk.v17i1.6966